The role of copeptin as a novel cardiovascular biomarker (Faculty of Medicine Universitas Indonesia, 2015)
Copeptin is a provasopressin-derived peptide, the precursor for arginine vasopressin (AVP), which is an antidiuretic hormone from the hypothalamus. Copeptin is secreted together with AVP equally as a response of AVP stimulation. While AVP’s main function is water and blood volume regulation and maintaining electrolyte homeostasis, copeptin’s function is still not fully understood. AVP, copeptin, and other vasopressinergic neuropeptides’ levels are elevated in acute stress caused by pathological conditions. Clinical use of AVP levels has many weaknesses. Copeptin can act as a replacement because of its molecular stability, easier testing methods, and faster results. For example, combination of copeptin and cardiac troponins can eliminate myocardial infarction (MI) diagnosis faster, while combined with brain-type natriuretic peptide (BNP) or its precursor can predict heart failure (HF) outcome. In cardiovascular shock, copeptin levels are elevated. As such, copeptin is a potential biomarker for MI diagnosis and predictor for HF mortality and morbidity.